2009
DOI: 10.1017/s1751731108003340
|View full text |Cite
|
Sign up to set email alerts
|

Diet learning through post-ingestive consequences in sheep: the case of starch and casein variously combined in the same foods

Abstract: Ruminants generally succeed in selecting an appropriate diet relative to their nutrient requirements, and macronutrients such as energy and protein are considered as playing a primary role in their food preferences. Diet learning through post-ingestive consequences, evidenced by many studies that involved situations with simple discrimination tasks, may explain this ability to select a suitable diet. However, in more complex feeding environments where animals are faced with many plants varying both in their en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…glucose, Burritt and Provenza 1992), protein rewards (e.g. casein, Arsenos and Kyriazakis 1999;Ginane et al 2009), mineral rewards (e.g. phosphorus, Villalba et al 2006) and, as recently found, vitamin E (D Amanoel, DT Thomas, D Blache, JTB Milton, MG Wilmot, DK Revell, HC Norman, unpubl.…”
Section: Reward Regulation Of Food Intake In Ruminantsmentioning
confidence: 59%
“…glucose, Burritt and Provenza 1992), protein rewards (e.g. casein, Arsenos and Kyriazakis 1999;Ginane et al 2009), mineral rewards (e.g. phosphorus, Villalba et al 2006) and, as recently found, vitamin E (D Amanoel, DT Thomas, D Blache, JTB Milton, MG Wilmot, DK Revell, HC Norman, unpubl.…”
Section: Reward Regulation Of Food Intake In Ruminantsmentioning
confidence: 59%
“…Ces résultats illustrent aussi que l'encombrement, principal facteur du contrôle quantitatif de l'ingestion des fourrages, peut être modulé par les caractéristiques des aliments de la ration au travers des interactions qui trouvent leur origine dans la perception que les animaux ont des aliments (Ginane et al 2009). Ils montrent que la composante hédonique des choix alimentaires va au-delà des seuls facteurs digestifs et nutritionnels avec pour conséquence la moindre valorisation de l'ensemble de l'offre fourragère (Favreau et al 2010).…”
Section: A) Conséquences Sur L'ingestion Et Les Performances Des Géniunclassified